1998
DOI: 10.1148/radiology.209.1.9769827
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral obstructions and leaks after renal transplantation: outcome of percutaneous antegrade ureteral stent placement in 44 patients.

Abstract: Ureteral stents are safe and effective for the treatment of obstructions and leaks and are particularly effective for early and UNC obstructions. These stents may also be useful for temporary drainage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(26 citation statements)
references
References 0 publications
0
25
0
1
Order By: Relevance
“…First-line treatment for a complication usually consists of decompression and drainage via nephrostomy tube, retrograde double J stenting, or balloon dilation. All of these techniques have moderate short-term success rates of 39-86.7% (19)(20)(21)(22)(23) but are often not a durable solution due to recurrent infections associated with the hardware and high restenosis rates after dilatation. Late ureteral stenosis is even more recalcitrant to temporizing interventions (recurrence rates between 40 and 44%) (19,20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First-line treatment for a complication usually consists of decompression and drainage via nephrostomy tube, retrograde double J stenting, or balloon dilation. All of these techniques have moderate short-term success rates of 39-86.7% (19)(20)(21)(22)(23) but are often not a durable solution due to recurrent infections associated with the hardware and high restenosis rates after dilatation. Late ureteral stenosis is even more recalcitrant to temporizing interventions (recurrence rates between 40 and 44%) (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…All of these techniques have moderate short-term success rates of 39-86.7% (19)(20)(21)(22)(23) but are often not a durable solution due to recurrent infections associated with the hardware and high restenosis rates after dilatation. Late ureteral stenosis is even more recalcitrant to temporizing interventions (recurrence rates between 40 and 44%) (19,20). We believe that early surgical intervention offers a more consistent and durable solution and can potentially prevent renal allograft injury due to recurrent pyelonephritis and hydronephrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, there have been many reports of successful percutaneous antegrade endoluminal balloon dilatation of transplant ureteric stenosis, with success rates of 43-89%. And many investigators have reported a higher success rate for balloon dilatation in patients with early obstruction ( < 3 months after transplantation) compared with those with late obstruction ( > 3 months after transplantation) [6,7]. This difference might be attributed to the ischaemic fibrosis, which is the main reason for the late obstruction whereas early obstruction might be secondary to mechanical causes such as oedema, blood clots, or a restricting submucosal tunnel.…”
Section: Discussionmentioning
confidence: 99%
“…[9] reported that 13 patients underwent dilatation with (nine patients) or with no (four) diathermic incision, only the four patients treated with dilatation had recurrent obstruction, while the nine treated with dilatation and incision had no obstruction recurrence (mean follow-up 58 months, range there was no recurrence of obstruction in six of eight patients. The outcomes of published reports (with more than five patients) on endoscopic management for ureteric obstruction in transplanted kidneys are summarized in Table 2 [6,7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The total long-term success rate was 68%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation